Basal ganglia circuits for reward value-guided behavior - Hikosaka, Okihide; Kim, Hyoung F; Yasuda, Masaharu; Yamamoto, Shinya (Annual review of neuroscience, 2014)
The basal ganglia are equipped with inhibitory and disinhibitory mechanisms that enable a subject to choose valuable objects and actions. Notably, a value can be determined flexibly by recent experience or stably by prolonged experience. Recent studies have revealed that the head and tail of the caudate nucleus selectively and differentially process flexible and stable values of visual objects. These signals are sent to the superior colliculus through different parts of the substantia nigra so that the animal looks preferentially at high-valued objects, but in different manners. Thus, relying on short-term value memories, the caudate head circuit allows the subject's gaze to move expectantly to recently valued objects. Relying on long-term value memories, the caudate tail circuit allows the subject's gaze to move automatically to previously valued objects. The basal ganglia also contain an equivalent parallel mechanism for action values. Such flexible-stable parallel mechanisms for object and action values create a highly adaptable system for decision making.